(untitled) (Medico Legal Update, 2021)
Background: Autologous bone marrow transplantation is a curative procedure forhematological diseases and immune deficiencies. The unique and intensive nature of this treatment requires distinctive care during and post the entire transplant course. Nursing intervention for caregivers post autologous bone marrow transplantation patients at home is an important component of the care that improves and develops knowledge and practice of the caregivers, to take care of the patients in order to help them followthe demanding treatment plan to reach recovery. Aim to evaluate the effect of nursing intervention for caregivers of post-autologous bone marrow transplantation patients at home. Material and Method: A Quasi-experimental study was carried out among convenient sample of 143 patients and their caregivers who attended the follow up clinic during the first six months post autologous bone marrow transplantation. The study was conducted among patients and their caregivers in three different hospitals Sheikh Zayed Specialized Hospital, National oncology institute, and Nasser institute at outpatient’s follow-up clinics.A self-administered questionnaire of patients and their caregivers’ demographic data, and reported checklist of caregivers’ knowledge and practices toward post-autologous bone marrow transplantation patients at home. Results: There was astatistically significant difference between pre and post nursing intervention, which indicate improvement in caregivers’ knowledge and practice post implementation of the nursing intervention program, and positive correlation between their knowledge and practice. Conclusion and Recommendations: Although caregivers had adequate knowledge, practice on some aspects, gaps were identified. There is a need for educational interventions and discharge plan to upgrade knowledge and practices of the caregivers of post autologous bone marrow transplantation patient at home.